Studies on the Preparation of Functional Fish Protein Concentrate from Nemipterus japonicus by Enzymatic Method - T., Mahesh; T.M.R., Setty; T.S., Shetty; C.N., Ravishankar (Fishery Technology, 2025)
The study was carried out to develop a suitable method for the preparation of functional fish protein concentrate(FFPC) from theundcrutilized fish, Japanese threadfin bream (Nemipterus japonicus) and to evaluate their functional properties, sensory and chemical characteristics. The FFPCs were prepared employing proteolytic enzymes to partially hydrolyse proteins and then dried in vacuum as well as in a spray drier. The FFPCs obtained by Â· these processes exhibited better functional and sensory properties when oompared to oon- ventionally prepared fish protein concentrate.